Praktik Endorsement oleh Influencer Tiktok Perspektif Akad Ijarah dan Fatwa MUI Nomor 24 Tahun 2017 tentang Hukum dan Pedoman Bermuamalah melalui Media Sosial - Suryaningtiyas, Adhiva Nurul Amalia (Maliyah : Jurnal Hukum Bisnis Islam, 2022)
This research discusses endorsement practices by TikTok influencers and how to analyze the Ijarah contract and DSN MUI Fatwa Number 24 of 2017 on endorsements by influencers in the TikTok application. This research is qualitative research with a descriptive approach. The results of this study show that the endorsement system carried out by "GR" on TikTok is to provide several service packages at different rates. After the endorser is sure that he agrees and fills in the endorser's format, he can send fees according to the selected package via transfer. Then, the admin will send an address for the endorser to send the item to be endorsed. After that, the endorsement process will be executed. However, the focus of the problem is the need for certainty regarding the estimated upload video endorsement after payment has been made. This is inconsistent with the point that benefits must be explicitly known and clearly to avoid disputes. The endorsement system carried out can be said to follow the provisions of Islamic law in general regarding the pillars of ijarah, but not with the specific terms of ijarah. Meanwhile, according to the general guidelines and guidelines for creating content/information in the DSN MUI Fatwa Number 24 of 2017 concerning Law and Guidelines for Muamalah through Social Media, the practice of endorsement carried out by "GR" influencers so far is considered to be less following the provisions in point " produce and/or disseminate content/information with the aim of justifying what is wrong or blaming the right, building opinions so that they appear to be successful and successful, and the aim is to hide the truth and deceive the public" in the fatwa.